Perception and Attitude towards Disaster Preparedness among Library Professionals in University of Kerala and University of Calicut: An Investigative Study - Selin, Ancy S.; Devi, B. Mini (Journal of Information and Knowledge, 2024)
Libraries stand as crucial pillars in moulding the future generations of society, playing a foundational role in the socioeconomic development of nations. Recognizing their significance, it becomes imperative to safeguard libraries for the prosperity of the upcoming generations. Central to this responsibility is the need for libraries to be well-equipped and prepared to face potential disasters. The article delves into the study of the perception and attitude of library professionals towards disaster preparedness at the University of Kerala and the University of Calicut. The objectives encompass assessing librarians’ perception levels, examining current disaster precautions, studying awareness about disaster management authorities, evaluating awareness of rules and laws, and determining the existence of structured training programs. To gather relevant literature, diverse resources such as Google Scholar, Emerald, ProQuest, ResearchGate, ScienceDirect, conference proceedings, dissertations and theses in Library and Information Science were consulted. The study utilised a closed-ended structured questionnaire aligned with the defined objectives to collect data. The gathered data underwent tabulation and analysis using Microsoft Excel 2013 and SPSS version 21. The findings of the study revealed that library professionals possess an awareness of disasters and the necessity for preparedness, yet there seems to be a gap in translating this knowledge into practical implementation. The conclusion drawn is a call to action, emphasising the need for libraries to execute disaster awareness and training programs for both staff and users. In a world where natural calamities and unforeseen events pose a constant threat, understanding how library professionals perceive and approach disaster preparedness becomes paramount. As custodians of academic treasures, their perspectives shape the resilience of these institutions against potential disruptions. The study, therefore, serves as a critical exploration into the preparedness landscape, providing insights that extend beyond the immediate scope of libraries to contribute to the broader discourse on disaster management in academic settings.